Electrophysiological monitoring of injury progression in the rat cerebellar cortex - Ordek, Gokhan; Proddutur, Archana; Santhakumar, Vijayalakshmi; Pfister, Bryan J.; Sahin, Mesut (Frontiers in Systems Neuroscience, 2014)
The changes of excitability in affected neural networks can be used as a marker to study the temporal course of traumatic brain injury (TBI). The cerebellum is an ideal platform to study brain injury mechanisms at the network level using the electrophysiological methods. Within its crystalline morphology, the cerebellar cortex contains highly organized topographical subunits that are defined by two main inputs, the climbing and mossy fibers. Here we demonstrate the use of cerebellar evoked potentials (EPs) mediated through these afferent systems for monitoring the injury progression in a rat model of fluid percussion injury (FPI). A mechanical tap on the dorsal hand was used as a stimulus, and EPs were recorded from the paramedian lobule (PML) of the posterior cerebellum via multi-electrode arrays (MEA). Post-injury evoked response amplitudes (EPAs) were analyzed on a daily basis for one week and compared with pre-injury values. We found a trend of consistently decreasing EPAs in all nine animals, losing as much as 72±4% of baseline amplitudes measured before the injury. Notably, our results highlighted two particular time windows; the first 24 hours of injury in the acute period and day-3 to day-7 in the delayed period where the largest drops (~50% and 24%) were observed in the EPAs. In addition, cross-correlations of spontaneous signals between electrode pairs declined (from 0.47±0.1 to 0.35±0.04, p<0.001) along with the EPAs throughout the week of injury. In support of the electrophysiological findings, immunohistochemical analysis at day-7 post-injury showed detectable Purkinje cell loss at low FPI pressures and more with the largest pressures used. Our results suggest that sensory evoked potentials recorded from the cerebellar surface can be a useful technique to monitor the course of cerebellar injury and identify the phases of injury progression even at mild levels.